2012
DOI: 10.1242/dev.075846
|View full text |Cite
|
Sign up to set email alerts
|

DAZL is essential for stress granule formation implicated in germ cell survival upon heat stress

Abstract: SUMMARYMammalian male germ cells should be maintained below body temperature for proper development. Here, we investigated how male germ cells respond to heat stress. A short exposure of mouse testes to core body temperature induced phosphorylation of eIF2 and the formation of stress granules (SGs) in male germ cells. We observed that DAZL, a germ cell-specific translational regulator, was translocated to SGs upon heat stress. Furthermore, SG assembly activity was significantly diminished in the early male ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
90
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 57 publications
(84 reference statements)
10
90
0
Order By: Relevance
“…Thus, the dynamic cycle of SG assembly/disassembly can be viewed as a strategy to cope with disruptions in translation caused by environmental stress. In keeping with this view, cells with impairments in SG assembly show decreased ability to survive exposure to stressful stimuli (1)(2)(3).…”
mentioning
confidence: 68%
“…Thus, the dynamic cycle of SG assembly/disassembly can be viewed as a strategy to cope with disruptions in translation caused by environmental stress. In keeping with this view, cells with impairments in SG assembly show decreased ability to survive exposure to stressful stimuli (1)(2)(3).…”
mentioning
confidence: 68%
“…In addition to these proteins, the ubiquitous category is highly enriched with the components of the spliceosome (SRSF9, SRSF2, U2AF1, HNRNPL) and proteasome (UBC, UBE2I, UBE2D3). Majority of the RBPs (60%) constituted tissue-specific category ( Figure 4C) and included heat response protein 12, HRSP12, known to be expressed in kidney and liver [60], DAZL -a germ cell specific RBP [61], member of the CELF family CELF3 that is highly expressed in brain [62], PUF60-poly-U binding splicing factor 60kDa, that was recently shown to be required for the splicing of a subset of tissue-specific splicing events which when deregulated in the absence of PUF60 affect the development of organs such as brain, heart, kidney and eye [63]. Analysis of the comparison of expression patterns of classical and non-classical RBPs in each of the 16 tissues revealed that in ~50% of the tissues, the expression of non-classical RBPs was significantly higher than the classical RBPs (p<0.05, Wilcoxon test) ( Figure 4D).…”
Section: Majority Of the Rbps Exhibit Tissue-specific Protein Expressmentioning
confidence: 99%
“…In addition, other cellular proteins could be packed into stress granules, including Tudor Staphylococcal Nuclease (Tudor-SN, also known as SND1), adenosine deaminase acting on RNA 1 (ADAR1) (Weissbach and Scadden, 2012), DAZL (Kim et al, 2012), p90 ribosomal S6 kinase 2 (RSK2, also known as RPS6KA3), Ras homolog gene family member A and Rho-associated coiled-coil forming kinase 1 (RhoA and ROCK1) (Tsai and Wei, 2010), 2-oxoglutarate and Fe(II)-dependent oxygenase domain containing 1 (OGFOD1) (Wehner et al, 2010), melanoma differentiationassociated gene 5 (MDA5, also known as IFIH1) and retinoicacid-inducible gene I (RIG-I, also known as DDX58) (Langereis et al, 2013;Onomoto et al, 2012). When conditions that are suitable for translation are restored, the components of stress granules are dynamically released so that translation is rapidly resumed.…”
Section: Introductionmentioning
confidence: 99%